If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5b + -6 + -9b + -8 = 0 Reorder the terms: -6 + -8 + 5b + -9b = 0 Combine like terms: -6 + -8 = -14 -14 + 5b + -9b = 0 Combine like terms: 5b + -9b = -4b -14 + -4b = 0 Solving -14 + -4b = 0 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '14' to each side of the equation. -14 + 14 + -4b = 0 + 14 Combine like terms: -14 + 14 = 0 0 + -4b = 0 + 14 -4b = 0 + 14 Combine like terms: 0 + 14 = 14 -4b = 14 Divide each side by '-4'. b = -3.5 Simplifying b = -3.5
| P=5x-2(50+x) | | 1+2a-7+9a+5=6a+8a-13+2-3a | | 34/35:(x-3)=17/25:2/5 | | P=5x-(10+2x) | | 1/6(-12x-11)= | | 3v^2+4=8v | | 200=3x+2y | | 30=-5(6n+2) | | 12x-3(3x-2)=2x+10 | | X-4y=-44 | | R^2/d^2=gt | | 7=1d-3 | | 5x-0.02+x=19.98 | | 1/6/5/18=2/5/n | | 2y=60-3x | | 2xsquared+5x=7 | | (5b^2-15)/(b-3) | | indices8x=1/4 | | -68+(-2)= | | f(x)=2x^2+8x+9 | | 2x+(x+42)=90 | | 5/a*a | | 24x-13=4(6x-3)-1 | | 8x+13=-7x-18 | | 5x(2+8)= | | -0.25x^2+3.25x=y | | N:1/2 | | 8s=6/5 | | -0.25x+3.25x=y | | 2x^2-9=91 | | 2y-(1/2)=10 | | 2a+3a=50 |